PENGARUH CITRA MEREK DAN KUALITAS INFORMASI TERHADAP MINAT KONSUMEN BERBELANJA KEMBALI DI ZALORA - Widiani, Ni Luh Mega; Indiani, Ni Luh Putu; Wahyuni, Ni Made (Jurnal Ilmiah Manajemen & Bisnis, 2019)
Online shopping activity is currently very popular in the societyas online shops offer attractive products and provide convenience when shopping. Zalora is a highly preferred online shop, as it achieved the highest top brand index for several. This study aimed to analyze factors that influence consumer intentionto shop at Zalora. This research was conducted in Denpasar. The population in this study are consumers in Denpasar who have shopped at Zalora in the past 1 year. Samples were 112 respondents. Data collection used survey method with questionnaire as instrument. Data was analyzed using multiple linear regression analysis. The results showed that brand image and information quality has a positive and significant impact on online purchase intention. To improve Brand Image, Zalora needs to provide frequent discounts, display detailed product information including high-resolution photos and ensure that it provides benefit and value to consumers. To improve the information quality, Zalora needs to ensure that product information is presented accurately and completely, present product information in an easily understood format, and send timely notifications about the order status.